Modeling of nonlinear clarification of aqueous suspensions at rapid filters - Поляков, Вадим (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The basic mathematical problem of nonlinear deep bed clarification of aqueous suspensions at rapid filters is formulated. The results of its solution using exact method for the linear form of the adhesion function and approximate method for the nonlinear form are selectively presented. The derived dependencies are illustrated by parallel exact and approximate calculations of the main filtration characteristics. An estimation of the сalculated errors due to simplification of the original model was carried out indicating the high accuracy of the approximate solution.